Perceived Time, Frequency, and Intensity of Engagement and Older Masters Athletes' Subjective Experiences - Deck, Sarah; Doherty, Alison; Hall, Craig; Schneider, Angela; Patil, Swarali; Belfry, Glen (Frontiers in Sports and Active Living, 2021)
Masters athletes are a unique group of older adults whose experiences may provide valuable insights into the role of sport for successful aging. The purpose of this study was to explore whether masters athletes' social and psychological experiences vary with their time, frequency, and perceived exertion in training and competition. Semi-structured interviews were conducted with 40 men and women older masters athletes, aged 50–79 years (M = 66), who were active at the competitive level across a variety of sports (e.g., volleyball, curling, rowing, dragon boating, running, swimming, and basketball) at the time of the study. Results indicate that all participants experienced social and psychological benefits from engaging in masters sport. Only the high-frequency engagement subgroup (participating five to seven times per week in training and/or competition) reported social downsides, in terms of missing time with family and friends outside of masters sport. However, some participants described the positive family support (e.g., spouse who endorses sport participation) that overrides some of the social costs. These findings have implications for realizing positive experiences with minimal engagement in masters sport, yet an apparent threshold of participation beyond which negative social consequences may be experienced. This is an important consideration for the design and promotion of sport for older adults.